A new species of Eupogoniopsis and new record of Eupromus ruber (Dalman) (Coleoptera: Cerambycidae) from South Korea. Issue 6 (25th November 2013) - Lim, Jongok; Lim, Jong‐Su; Lee, Bong‐Woo
Abstract Eupogoniopsis granulatus sp. nov., hosted on Broussonetia papyrifera (L.) L'Her. ex Vent. (Moraceae) is described based on a large number of specimens and the spotted scarlet longhorn beetle, Eupromus ruber (Dalman, 1817) is recorded from South Korea for the first time. Descriptions of the two species are provided with diagnostic illustrations including male genitalia for each species. A key to world species of Eupogoniopsis is also presented.